Microwave-assisted synthesis and characterization of antioxidant chitosan-based aerogels for biomedical applications. Issue 8 (17th November 2018) - Radwan-Pragłowska, Julia; Piątkowski, Marek; Janus, Łukasz; Bogdał, Dariusz; Matysek, Dalibor; Cablik, Vladimir
Abstract: Rapid regenerative medicine development requires new advanced biomaterials. Chitosan which is known of its unique properties like biocompability, biodegradability, bioactivity, antibacterial activity is a great candidate for scaffolds for cell culture. In this paper, a novel strategy for antioxidant aerogels obtainment method is presented. Biomaterials were synthesized under microwave-assisted conditions and modified with Tiliaplatyphyllos extract. Ready products were characterized over their physicochemical properties, morphology and biological properties including bioactivity and antimicrobial activity. Performed analyses confirmed obtainment of crosslinked biomaterial with advanced properties such as positive effect on cells proliferation and inhibition of Staphylococcus aureus growth.